Analisis Sistem Jaminan Dalam Bagi Hasil Pada Perbankan Syariah - Nadhifah, Tuti; Risnawati, Heni; Mustaqim, Yunus; Roni, Abdul (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
This study aims to analyze the obligation to provide collateral in the profit sharing agreement in Islamic banks. In this study using a descriptive qualitative research approach that is through the study of literature and combined with theories relating to the obligation to provide collateral in the profit sharing agreement at Islamic banks. The results of this study are that the basis for the profit sharing agreement rests only on the principle of trustworthiness, but that does not mean that there should not be any collateral charged to customers in banking operations. This is because in the context of the guarantee agreement is done voluntarily between the parties, and contains a halal clause so that it can be concluded that the guarantee agreement in banking is a legal and lawful agreement.